Risk and poverty in agriculture: expanding roles for agricultural cooperatives in Malaysia - Okezie Chukwukere A; Amir Hussin Baharuddin (Faculty of Social Sciences and Humanities, UKM,Bangi, 2012)
The inter-relationship between risk, poverty and agriculture in development economics has gained increased attention. Agriculture in which the poor predominantly operate is a fragile and risk-prone sector. The risks range from the large (aggregate) ones to the small (idisyncratic).Aggregate risks such as droughts,cyclones,floods, and market fluctuations tend to affect the whole community simultaneously, while idisyncratic risks affect a particular household or individual such as with respect to illness, death, and disability. The contribution of Agricultural cooperatives as instruments of development has been widely acknowledged. This study highlights the role of agricultural cooperatives in tackling both risks and poverty in the Malaysian agriculture sector. It was found that with 5.685 million members, share capital amounting to RM 6.849 billion and total assets worth RM 34.868 billion the Malaysian agricultural cooperatives were well placed to manage poverty related risks afflicting local paddy farmers, fishermen and smallholders through their diverse functions in credit/finance, plantation, housing, consumer, transport and services. Nevertheless, in conclusion, to better harness their strength these cooperatives must be less dependent on government funding to gain better freedom from undue interferences.